Analysis of urinary calculi by physical methods in Hospital Universiti Sains Malaysia - Zainuddin, Saiful Azli Mohd (2010)
In urolithiasis or kidney stone disease, research and in clinical practice the highly specific and systematic analysis of urinary calculi is of great importance. The exact knowledge of the type of the stone is a precondition of any medical therapy for urinary calculus. Urolithiasis is a very frequent finding in the Kelantan, but stone analysis is not routinely performed in HUSM. Knowledge of the composition of calculi yields fundamental information concerning the pathogenesis of the disease, including metabolic abnormalities, presence of infection, possible artifacts, and even drug metabolism. Accurate high-quality urinary calculi analysis is an essential requirement for this approach to patient management, allowing possible causes to be defined, logical treatment strategies to be implemented and prevention of stone recurrence. Each method has merit in specific situations. Whereas a single method may not be adequate for all analyses, a combination of methods used in a complementary fashion may be relied on for accurate results. We therefore set out to analyze one hundred and fifty five samples of urinary calculi in HUSM using the modem physicochemical methods, X-ray diffraction, Fourier Transform Infrared Spectroscopy, Scanning electron microscopy and X-ray fluorescence which yield the best results in the differentiation of the constituents of urinary calculi. The objectives of this study are to determine the composition of urinary calculi in HUSM and correlate the urinary calculi composition using various techniques under physical methods. Apart from that, we would also like to determine the association of demographic features and location of the urinary stone formers. Last but not least, is to determine the agreement between these four methods. We study the results, the reliability of these methods and the important analytical tests for urinary calculi on identical stone material under routine conditions. Through accurate high-quality urinary calculi analysis, allowing logical treatment strategies to be implemented. This is an observational cross-sectional analytical study involves a total of one hundred and fifty five urinary stone formers in HUSM which were collected from January 2003 to December 2009. All stones removed from patients were placed in polyethylene dry bottles labeled with the name, identification number, hospital registration number, sex, age, date and ethnicity of the patient. The location of the stone and treatment were also recorded. Urinary calculi weighing more than 500mg were selected and prepared for the investigation. The specimens of urinary calculi were washed with distilled water, air-dried, finely ground and pressed into powder and divided into 4 samples and prepared for analysis using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and X-ray Fluorescence (XRF). All tests were performed at the Science Labs, School of Material and Mineral Resources Engineering, Engineering Campus USM Transkrian Penang.